Transformações de a gata borralheira em Cinderela: do conto ao cinema - PEREIRA, Leyslie de Oilveira Emiliano M. (2017)
This research intends to analyze, in a comparative way, film works that possibly are adaptations of the fairy tales, with the objective of investigating to what extent the differences in relation to the original work still allow one to call an adaptation film. Authors, such as Linda Hutcheon and Robert Stam, agree that faithfulness between works is no yardstick to say whether an adaptation is good or bad. But what elements can really be decisive for considering a work as an adaptation? In order to answer the research problem, the specificity of the fairy tales is studied, as well as to rescue the theories of adaptation applying the vision based on the following products: Cinderella (1950), Cinderella (2015), Uma Linda Mulher (1990), Sweet Asbestos (2013) and Shrek (2001), which were inspired by the short story Gata Borralheira by French author Charles Perrault.